Stunting Handling Patterns Through Meatball Food Intake (Processed Fish) at Bone Bolango Vocational School - Fitriyanti Thalib; dr Rita Amini; Frezy Paputungan (LP2M Universitas Bina Mandiri Gorontalo, 2023)
Stunting is a condition of failure to grow (growth faltering) in children under five due to chronic malnutrition, especially in the first 1,000 days of life (HPK). Stunting can affect brain growth and development. Stunted children also have a higher risk of suffering from chronic diseases in adulthood. Stunting describes chronic malnutrition status during growth and development since early life. There are several nutrients related to stunting such as protein and low parental knowledge in parenting, poverty, low environmental sanitation, low food accessibility at the family level, especially in poor families, low family access tobasic health services, and disparities between provinces that still exist. needs to be addressed with specific problems in vulnerable areas. Stunting is a sensitive indicator of poor socioeconomic status and a predictor of long-term morbidity and mortality. Stunting in early childhood is reversible.